Palm Trees, Dates, Milk and Honey: On Palm Trees and Dates (1967) — A Collection of Arab Folk Songs Translated by Nathan Zach and Rashid Hussein - Pridan, Ariel (MiKAN, 2022)
Offering a critical analysis of Palm Trees and Dates [1967 דקלים ותמרים )—a Hebrew translation of Arab folk songs by Nathan Zach and Rashid Hussein, this article suggests that this translation’s declared aim to generate a genuine Arab-Jewish dialogue cannot be fully achieved under a political climate that subordinates representations of the Arab subject to the ideological codes of Israeli sovereignty. A close readingreveals, not quite unsurprisingly, that the translated text carries Zach’s own poetic fingerprint. This testifies to the ways in which the translation draws its legitimacy from the subordination of the Arab folk songs to the poetic and aesthetic conventions of Israeli civic-poetry and its broad Jewish context. Despite its promising point of departure, this translation perpetuates the dominance and exclusiveness of Hebrew, the language of power, over Arabic, and enables the repression of the national “other” by presenting the Hebrew reader—the target recipient of this translation—with a familiar, easily recognizable, and non-threatening poetic world. In so doing, this translation does not express the existence of bilingualism as an egalitarian and democratic cultural option in the Israeli reality; rather, it inevitably undermines its potential to function, in Paul Ricoeur’s terms, as a genuine instance of “linguistic hospitality.”